North-South trade agreements and the quality of institutions: Panel data evidence - Sophie Therese Schneider (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Since 1990, not only the number of signed preferential trade agreements (PTAs) has increased, but also their depth. That means, PTAs include comprehensive rules, which go way beyond tariff reductions, such as property rights, competition or investment provisions. This paper argues that especially in North-South agreements there is a diffusion of institutional quality from developed to developing countries. First, a PTA may affect institutions because it can serve as a network for political exchange and second, the regulations and commitments stipulated in it may affect local institutions in the South. I empirically investigate if there are positive effects of being a member in a PTA on the quality of institutions in developing countries by accounting for the number and the depth of PTAs using the Design of Trade Agreements (DESTA) database, established by Dür, Baccini and Elsig (2014). I create a large panel data set covering 32 years to account for endogeneity of several controls. The results support the hypothesis that deep PTAs lead to an improved quality of institutions in the South. The results differ with respect to the type of agreement and region.
urn:nbn:de:bsz:100-opus-15773
Keywords: F13; F14; C23; C26; 330; deep trade agreements; institutions; panel data